Philosophy's nature - Trizio, Emiliano, author.
1 online resource.
Keywords: "This book offers a systematic interpretation of the relation between natural science and metaphysics in Husserl's phenomenology. It shows that Husserl's account of scientific knowledge is a radical alternative to established methods and frameworks in contemporary philosophy of science. The author's interpretation of Husserl's philosophy offers a critical reconstruction of the historical context from which his phenomenological approach developed, as well as new interpretations of key Husserlian concepts such as metaphysics, idealization, life-world, objectivism, crisis of the sciences, and historicity. The development of Husserl's philosophical project is marked by the tension between natural science and transcendental phenomenology. While natural science provides a paradigmatic case of the way in which transcendental phenomenology, ontology, empirical science, and metaphysics can be articulated, it has also been the object of philosophical misunderstandings that have determined the current cultural and philosophical crisis. This book demonstrates the ways in which Husserl shows that our conceptions of philosophy and of nature are inseparable. Philosophy's Nature will appeal to scholars and advanced students who are interested in Husserl and the relations between phenomenology, natural science, and metaphysics"--